[Greenhouses at Fludir] - Streng, Evelyn Fiedler (1975)
Photograph of greenhouses at Flúðir. White, pointed greenhouses sit in rows along a grassy plain surrounded by hills. A blue river crosses the photograph in the bottom right corner of the photograph. The village is visible in the background, surrounded by trees. A white tower sits atop the hill behind the greenhouses alongside trees and other buildings.